Effect of smoking on blood and semen lead level in male partners of infertile couple (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: blood lead levels; semen lead level; smoking in infertile patientdoi: 10.3329/jcmcta.v19i2.3862Journal of Chittagong Medical College Teachers' Association 2008: 19(2):3-6